Is Idiopathic Sudden Sensorineural Hearing Loss Seasonal?. Issue 9 (30th October 2022) - Simani, Liam; Oron, Yahav; Shapira, Udi; Handzel, Ophir; Abu Eta, Rani; Warshavsky, Anton; Horowitz, Gilad; Muhanna, Nidal; Shilo, Shahaf; Ungar, Omer J.
Abstract : Objective: To investigate the circannual rhythm (seasonal incidence) of idiopathic sudden sensorineural hearing loss (ISSNHL). Methods: Data were retrieved from the medical files of an original cohort of all consecutive patients with ISSNHL in a tertiary medical center between 2012 and 2020. A systematic literature search of "MEDLINE" via "PubMed, " "Embase, " and "Web of Science" on comparable published cases was performed. A Google Trends analysis of the term [sudden hearing loss] and related terms between 2014 and 2020 was also performed. Results: Most of the published series (9/12) reported the highest ISSNHL incidence in the spring and the lowest in the winter (8/12). In our local series, the incidence during the winter was significantly lower than that for the other seasons by a factor of 0.69 (95% confidence interval, 0.65–0.77; p = 0.041; r = 0.36). Google Trends data showed no significant correlation between the calendric month and the incidence of ISSNHL in any of the analyzed countries ( p = 0.873, r 2 = 0.029). Conclusion: The ISSNHL incidence was lowest during the winter season in our cohort and reported for other cohorts worldwide. Google Trends–based model analysis did not determine any circannual rhythm.